Estimating snow leopard and prey populations at large spatial scales. Issue 4 (9th December 2021) - Suryawanshi, Kulbhushansingh; Reddy, Abinand; Sharma, Manvi; Khanyari, Munib; Bijoor, Ajay; Rathore, Devika; Jaggi, Harman; Khara, Abhirup; Malgaonkar, Aditya; Ghoshal, Abhishek; Patel, Jenis; Mishra, Charudutt
Abstract: Effective management of charismatic large carnivores requires robust monitoring of their population at local, regional and global scales. While enormous progress has been made to estimate carnivore populations at local scales, estimates at regional and global scales remain elusive. In the first systematic effort at a large regional scale, we estimated the population of the elusive snow leopard Panthera uncia over an area of 26, 112 km 2 in the Indian state of Himachal Pradesh. We stratified the entire snow leopard habitat in Himachal Pradesh based on an occupancy survey. Subsequently, we conducted camera trapping surveys at 10 sites distributed proportionately, that is with similar coverage probability across the three strata. We conducted simulations to understand how unidentified captures could affect our model estimate. We also assessed populations of the primary wild ungulate prey of snow leopards – blue sheep Pseudois nayaur and Siberian ibex Capra sibirica . Our results yielded a mean estimated density of 0.19 (95% confidence interval [CI]: 0.12–0.31) snow leopards per 100 km 2 and population size of 51 (95% CI: 34–73) snow leopards in Himachal Pradesh. The density estimates for individual sites ranged from 0.08 to 0.37 snow leopards per 100 km 2 . Simulations showed that unidentified snow leopard captures did not seem to affect the accuracy of our model estimate but could have affected the precision. Wild ungulate prey density ranged from 0.11 to 1.09 per km 2 . Snow leopard density showed a positive linear relationship with prey density (slope = 0.25, SE = 0.08, P = 0.01, R 2 = 0.51). Our study shows the earlier opinion‐based estimate for Himachal Pradesh to have been significantly positively biased. Using occupancy surveys to stratify large areas in order to design camera trap surveys addresses one of the common spatial sampling biases, that is limited sampling of only prime snow leopard habitats. Our work validates two‐step approach recommended in the ongoing initiative of the 12 snow leopard range countries for Population Assessment of World's Snow leopards (PAWS program), and cautions against the use of opinion‐based estimates for assessing the status of species of critical conservation importance. Abstract : Estimating populations at large spatial scales can be challenging because of biases associated with limited sampling. We demonstrate a two‐step approach to estimate snow leopard and their prey populations that uses occupancy surveys to inform camera‐trapping survey design. We recommend using such robust sampling methods to estimate populations as opinion‐based population estimates for snow leopards are likely to be positively overestimated. Абстрактный: Эффективное управление крупными хищными животными требует тщательного мониторинга их популяции на местном, региональном и глобальном уровнях. Несмотря на то, что был достигнут огромный прогресс в оценке популяций хищников на локальном уровне, оценки в региональном и глобальном масштабах остаются слабыми. В рамках первой систематической работы на крупном региональном уровне мы оценили популяцию неуловимого снежного барса Panthera uncia на площади 26 112 км 2 в индийском штате Химачал‐Прадеш. Мы стратифицировали всю среду обитания снежного барса в Химачал‐Прадеше на основе исследования занятости территории. Впоследствии мы провели установку фотоловушек на 10 участках, распределенных пропорционально, то есть с одинаковой вероятностью охвата по трем слоям. Мы провели моделирование, чтобы понять, как неопознанные снимки особей могут повлиять на нашу оценку модели. Мы также оценили популяции основных диких копытных пищевых видов снежного барса ‐ голубого барана Pseudois nayaur и сибирского козерога Capra sibirica. Наши результаты дали среднюю расчетную плотность снежного барса 0.19 (95% CI: 0.12–0.31) на 100 км 2 и размер популяции 51 (95% CI 34–73) снежного барса в Химачал‐Прадеше. Оценки плотности для отдельных участков колеблются от 0, 08 до 0, 37 снежного барса на 100 км 2 . Моделирование показало, что неопознанные снимки снежного барса, похоже, не повлияли на правильность оценки нашей модели, но могли повлиять на точность. Плотность диких копытных варьировала от 0, 11 до 1, 09 на км 2 . Плотность снежного барса имеет прямую линейную зависимость от плотности пищевых видов (наклон = 0, 25, SE = 0, 08, P = 0, 01, R 2 = 0, 51). Наше исследование показывает, что более ранняя оценка штата Химачал‐Прадеш, основанная на мнениях, была существенно смещена в положительную сторону. Использование обследований занятости для стратификации больших территорий с целью разработки исследовании с использованием фотоловушек устраняет одну из распространенных систематических ошибок пространственной выборки, то есть ограниченную выборку только лучших местообитаний снежного барса. Наша работа подтверждает двухэтапный подход, рекомендованный в рамках текущей инициативы 12 стран ареала снежного барса по оценке численности снежного барса в мире (программа PAWS), и предостерегает от использования оценок, основанных на мнениях, для оценки состояния критически важных для сохранения видов. सार: 1. मांसभक्षी पशुओं के प्रभावी प्रबंधन के लिये यह आवश्यक है कि उनकी आबादी की जानकारी स्थानीय, राष्ट्रीय व वैश्विक स्तर पर लगातार ली जाये। जबकि स्थानीय स्तर पर मांसभक्षी पशुओं की आबादी की जाँच लगातार की जा रही है, राष्ट्रीय व वैश्विक स्तर पर यह अभी भी नहीं हो रहा है। इस संदर्भ में, हमने एक बड़े स्थानीय स्तर पर हिम तेंदुए (Snow Leopard, Panthera uncia ) की आबादी की जाँच 26, 112 km 2 वर्ग में भारत के हिमाचल प्रदेश प्रांत में की। 2. आवासीय सर्वेक्षण के आधार पर हमने हिम तेंदुए (snow leopard) के प्राकृतिक वास को विभाजित किया। इसके बाद हमने 10 स्थलों पर कैमरा ट्रैप की मदद से आबादी की जाँच की। यह 10 स्थल ऐसे चुने गए थे की तीनों विभाजित क्षेत्रों में समान सर्वेक्षण किया जा सके। हमने सिमुलेशन कर यह भी अनुमान लगाया कि जो तेन्दुए विशिष्ठ रुप से पहचाने नहीं जा सकते उनका कैप्चर किस प्रकार हमारे आँकड़ों को प्रभावित करेंगी। हमने हिम तेंदुए के प्रमुख भोजन ‐ ब्लु शीप (Psuedois nayaur) एवं साइबेरियन आइबेक्स ( Capra sibirica) की आबादी का भी सर्वेक्षण किया। 3. हमारे परिणामों के अनुसार हिमाचल प्रदेश में हिम तेन्दुओं का औसत अनुमानित घनत्व 0.19 (95% CI: 0.12–0.31) प्रति 100 km 2 वर्ग हैं एवं आबादी संख्या 51 (95% CI 34–73) है। प्रत्येक साइट पर तेंदुओं का अनुमानित घनत्व 0.08 से 0.37 प्रति 100 km 2 वर्ग था। सिमु्लेशन के द्वारा हमें यह पता लगा कि जो तेन्दुए विशिष्ठ रुप से पहचाने नहीं जा सकते उनके कैप्चर से अनुमानित आँकड़ो पर तो प्रभाव नहीं पड़ा परन्तु वास्तविक आँकड़ो पर असर हो सकता है। जंगली खुर‐वाले जीवों की आबादी 0.11 से 1.09 प्रति km 2 पाई गई। हिम तेन्दुओं की संख्या शिकार की संख्या घनत्व के साथ‐साथ रैखिक रूप से बढ़ती हुई दिखाई दी (slope = 0.25, SE = 0.08, P = 0.01, R 2 = 0.51)। 4. हमारी शोध से पता चलता है कि पूर्व में हिमाचल प्रदेश में किये गये अभिमत‐अनुसार आकलन सकरातम्क पूर्वाग्रह (positive bias) रखते हैं। आवासीय आकलन के अनुसार बड़े इलाकों का विभाजन, फिर कैमरा ट्रैप से निरिक्षण एक आम स्पेशियल सैम्पल पूर्वाग्रह (bias) दर्शाता है ‐ केवल उन्हीं जगहों का नीरिक्षण जहाँ हिम तेन्दुओं की संख्या अधिक है। हमारा कार्य यह सिद्ध करता है कि 12 लेपर्ड रेंज देशों के Population Assessment of World's Snow leopards (PAWS program) द्वारा निर्धारित २‐स्टेप प्रस्ताव आकलन का सही माध्यम है एवं अभिमत‐अनुसार आकलन ना करना ही उचित है विशेषकर उन जीवों के लिये जो विकट संरक्षण श्रेणी में आते हैं।